A Structural Equation Model of Fund Management and Member Self-Reliance in Thai Village Financial Institutions: A Case Study of the Ban Huai Thuan Village Fund - Tavarom, Ausanakorn; Luengalongkot, Pongsatean (Journal of Population and Social Studies [JPSS], 2025)
Community financial organizations create capital systems, developing grassroots economies while village funds strengthen members’ self-reliance. This study aimed to analyze the consistency of the member self-reliance model and examine the direct, indirect, and total associations between the proposed factors and the self-reliance of Ban Huai Thuan Village Fund members. Using simple random sampling, 260 fund members completed questionnaires. Data analysis employed Structural Equation Modeling to examine model consistency between the proposed model and the empirical data, as well as to explore the associations among variables. Results demonstrated that a structural equation model of fund management and member self-reliance in Thai Village Financial Institutions is consistent with empirical data, as indicated by indices: χ² = 54.847, df = 42, p value = .0883, χ²/df = 1.305, CFI = 0.996, TLI = 0.992, RMSEA = 0.034, SRMR = 0.026. It was also found that fund management and the strength of the fund are positively associated with member self-reliance. Fund management is positively related to the strength of the fund and is indirectly associated with member self-reliance through its relationship with fund strength. Fund management shows the strongest association with member self-reliance, followed by fund strength.